Anthropometric study of cephalic index among medical students in Nepal - Timsina, Ram Prasad; Gogoi, Paramananda (Journal of Kathmandu Medical College, 2014)
Background: Cephalic index is the ratio of the maximum breadth of head to its maximum length that is expressed as a percentage. Anthropometric measurements, especially craniofacial measurements, are important for determining various head and face shapes. These anthropometric studies are conducted on the age, sex and racial/ethnic groups in certain geographical zones. Objectives: The objectives of this study were to find out racial classification and their differences in Nepalese medical students anthropologically and to compare these with the data from other ethnic caste for use in anthropometric and forensic studies. Method: This is a descriptive and cross sectional study on 940 undergraduate medical students of age 17 to 27 years, with 455 males and 485 females from the three different medical colleges of Nepal. The head length (cm) and breadth (cm) were measured by spreading calliper. The height (cm) and weight of the participants were recorded. All the collected data were summarized using statistical package for social sciences (SPSS) 16.0 versions and their significance was tested by student t-test. Results: The mean cephalic index of 455 males and 485 females were 80.99% and 83.34% respectively. The cephalic index varied from the range of 71.20 to 97.40 in female and 72.08 to 96.77 in male. The dominant type of head shape in our study was mesocephalic (50.76%) followed by brachycephalic (32.74%). Conclusion: This study showed the head type of Nepalese was brachycephalic predominant but with the tendency to mesocephalic and hyperbrachycephalic. DOI: http://dx.doi.org/10.3126/jkmc.v3i2.11229 Journal of Kathmandu Medical College Vol. 3, No. 2, Issue 8, Apr.-Jun., 2014 Page: 68-71